Perception and Behavior Analysis of Comorians Citizens on the Solid Household Waste Problems - Ali Issihaka Ali; Fadoua Karouach; Nabila Lahboubi; Mohammed Bakraoui; Hassan El Bari (European Scientific Journal, ESJ, 2018)
The objective of this study is to analyze the perception of Comorian citizens facing the situation of solid waste management (SWM). For this, a qualitative and quantitative approach is conducted on a sample of 300 households. The study shows that 61.1% of households freely dispose a waste on sensitive sites, 19.7% bring waste to collection points and 18.6% benefit from door-to-door. Moreover, 63% of households prefer door-to-door as a means of waste disposal compared to 19.5% who prefer voluntary intake and 17.5% prefer free evacuation. Home sorting concerns only 19.3% of households compared with 80.7% whose dispose mixed waste. Households that are aware of the negative impact of waste on health are 87.5%, against 5%, are unconscious and 7.5% remain without opinion. The study also shows that 40% of households are aware of the negative impact of waste on the environment, against 33% of non-conscious and 27% of non-opinion. The majority of households (58%) are unsatisfied of waste collection services schedules. However, 93.3% of households approve actions carried out by NGO and association. A financial contribution for waste management system improvement of 0.54 USD and 1.08 USD per month was approved by 67% of households.